Explorative study on Lactobacillus species and their acid‐producing capacity and anti‐microbial activity in head and neck cancer patients - Matilda Rahne; Amina Basic; Annica Almståhl (Wiley, 2021)
Abstract Objective To determine acid‐producing capacity and anti‐microbial activity of Lactobacillus species collected pretreatment and post treatment in head and neck cancer patients. Material and Methods Lactobacillus isolates from 21 patients pretreatment and post treatment were identified using molecular methods. The patients' stimulated salivary secretion was determined pretreatment, and 6 and 12 months post treatment and caries lesions/new filled surfaces registered at 24 months post treatment. The acid‐producing capacity of the Lactobacillus isolate was analyzed using a colorimetric fermentation test in microtiter plates. The anti‐microbial activity of the isolates against Streptococcus mutans associated with caries, and against the mucosal pathogens Staphylococcus aureus, Candida albicans, and Enterococcus faecalis was analyzed by determining inhibitory zones on agar plates. Results The most frequent species were L. paracasei (n = 21), L. casei/rhamnosus (n = 17) and L. fermentum (n = 10). Sixty‐seven percent of the patients harbored L. paracasei either at 6 or 12 months post radiotherapy. The corresponding figures for L. casei/rhamnosus and L. fermentum were 62% and 33%. L. paracasei strains showed the best acid‐producing capacity and L. fermentum strains the lowest. Strong acid‐producing capacity was most common among isolates collected at 6 months post treatment. Seventy‐two percent of the strains showed an anti‐microbial activity against S. mutans, one strain against S. aureus and none against C. albicans or E. faecalis. Conclusion The most frequent species isolated from head and neck cancer patients both pretreatment and post treatment were L. paracasei, L. casei/rhamnosus, and L. fermentum. L. paracasei showed the best acid‐producing capacity and the highest proportion with anti‐microbial activity against S. mutans.